2008
DOI: 10.1177/097185240901200302
|View full text |Cite
|
Sign up to set email alerts
|

Practices of Male Labor Migration from the Hills of Nepal to India in Development Discourses: Which Pathology?

Abstract: This article provides a critique of authoritative development discourses on the migration of men from Nepal's to India. Drawing from my ethnographic fieldwork at multiple sites, I illustrate how migration is not perceived as a problem by migrants themselves but as an integral practice in people's livelihoods. Many see migration to work in India as an escape from a difficult socioeconomic , cultural and familial situation and an opportunity for young men to experience a distant place, experiment with the pleasu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
38
0
4

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(42 citation statements)
references
References 21 publications
0
38
0
4
Order By: Relevance
“…Sharma's research highlights the importance of masculinity in explaining mobility and what it means for local communities. The importance of masculinity in relation to mobility is reflected in my fieldwork, as I found that only Kamaiya men move, something not explicitly considered in previous research on this or the wider Tharu community (although Sharma (2007aSharma ( , 2007bSharma ( , 2008) does consider this within predominantly high-caste communities in west-central hills in Nepal). However, in Sharma's research, he does not consider or complicate notions of hegemony and subaltern in relation to masculinity, something this article does through considering that these two seemingly contrasting types of masculinity can in fact be the same, but find different meanings in different contexts.…”
Section: Mobility and Masculinitymentioning
confidence: 87%
“…Sharma's research highlights the importance of masculinity in explaining mobility and what it means for local communities. The importance of masculinity in relation to mobility is reflected in my fieldwork, as I found that only Kamaiya men move, something not explicitly considered in previous research on this or the wider Tharu community (although Sharma (2007aSharma ( , 2007bSharma ( , 2008) does consider this within predominantly high-caste communities in west-central hills in Nepal). However, in Sharma's research, he does not consider or complicate notions of hegemony and subaltern in relation to masculinity, something this article does through considering that these two seemingly contrasting types of masculinity can in fact be the same, but find different meanings in different contexts.…”
Section: Mobility and Masculinitymentioning
confidence: 87%
“…Next to political and economic instability, migration has been also a -rite of passage‖ being particularly for young men central to their transition into adulthood [24,25], as well as a door-opener to formal and informal education and gaining the experience that is central to further mobility [26]. International migration from Nepal has increased steadily in recent decades, and officially 7.5% of the total population of 28 million are now absentees.…”
Section: Inequalities In Access To Migration and Its Benefitsmentioning
confidence: 99%
“…Nevertheless, such -ruralness‖ is still often equated with agriculture. Despite suggestions by scholars to revise the relevance of agriculture, policymakers and researchers have long focused overly on agriculture while ignoring the relevance of remittances and their social and economic impacts beyond financial flows [25,[42][43][44].…”
Section: Inequalities In Access To Migration and Its Benefitsmentioning
confidence: 99%
“…Mobility of people has altered the land-people nexus; it has changed the demand and value of land and reshaped the decision of people on acquisition, distribution and utilization of land. The existing literature mainly focuses on the drivers and process of migration, changing household consumption, transfer and use of remittances, and socioeconomic implications of migration [12][13][14][15][16]. However, the studies on how labour out-migration has played a role in acquisition, distribution, and utilization of land are still lacking.…”
Section: Introductionmentioning
confidence: 99%